LINC-08. Neuro-Oncology tumor board – one-year experience of international collaboration. (3rd June 2022) - Shatara, Margaret; Cantor, Evan; Meyer, Ashley; Ogle, Andrea; Hofmann, Kimberly; Green, Tammy; Beck, Mary; McHugh, Michele; Brossier, Nicole; Cluster, Andrew; Mian, Ali; Dahiya, Sonika; et al.
Abstract: BACKGROUND : The management of childhood central nervous system (CNS) tumors is complex and often faces numerous challenges in low- and middle- income countries (LMICs), including delayed diagnosis and limited treatment resources. Twinning initiatives between LMICs with high- income countries are feasible and proven to be highly effective at exchanging skills and expertise to improve diagnosis, treatment and care for children with brain tumors. METHODS : A monthly multidisciplinary international pediatric neuro-oncology tumor board via zoom videoconferencing was established in January 2021. This effort is a collaboration between Washington University School of Medicine, in St. Louis, Missouri, USA and nine international sites. Given the significant contributions of this international effort, it has since grown to include 20 institutions and cancer centers from 12 countries in the Middle East, Europe, Australia and South America. RESULTS : As of January 2022, we have held 11 tumor boards, 35 cases were reviewed, and have had 320 experts attend from several specialties – neuro-oncology, neurology, neurosurgery, neuroradiology and neuropathology. A multidisciplinary team of physicians reviewed each case and recommendations were given accordingly. We also started a quarterly neurofibromatosis (NF) meeting focused to leverage the expertise of dedicated specialists in the NF center. Two NF-focused meetings took place since establishing the program, and total of five cases were discussed. CONCLUSION : Virtual videoconferencing promotes a multi-disciplinary approach for the management of pediatric CNS tumors, and it allows access for medical expertise. We anticipate the current initiative will also provide a platform for future international research collaborations and deliver the optimal medical care for neuro-oncology patients globally. Multiple potential collaborative projects are currently underway.